Emission minimization of a top-lit updraft gasifier cookstove based on experiments and detailed CFD analyses. (1st November 2021) - Scharler, Robert; Archan, Georg; Rakos, Christian; von Berg, Lukas; Lello, Dave; Hochenauer, Christoph; Anca-Couce, Andrés
Graphical abstract: Abstract: Around 2.7 billion people worldwide have no access to clean cooking equipment, which leads to major health problems due to high emissions of unburned products (VOC, CO and soot). A top-lit updraft gasifier cookstove with forced draft was identified as the technology with the highest potential for reducing harmful emissions from incomplete combustion in simple cookstoves. The basic variant of the stove was equipped with a fan for efficient mixing of product gas with air and fired with pellets to increase the energy density of low-grade residues. The development was conducted based on water boiling test experiments for wood and rice hull pellets and targeted CFD simulations of flow, heat transfer and gas phase combustion with a comprehensive description of the reaction kinetics, which were validated by the experiments. Emphasis was put on the reduction of CO emissions as an indicator for the burnout quality of the flue gas. The optimisation was carried out in several steps, the main improvements being the design of a sufficiently large post-combustion chamber and a supply of an appropriate amount of primary air for a more stable fuel gasification. The experiments showed CO emissions <0.2 g/MJdel for wood and rice hull pellets, which corresponds to a reduction by a factor of about 15 to 20 compared to the basic forced draft stove concept. Furthermore, these values are between 5 and 10 times lower than published water boiling test results of the best available cookstove technologies and are already close to the range of automatic pellet furnaces for domestic heating, which are considered to be the benchmark for the best possible reduction of CO emissions.